Yes, we should discount the far-distant future at its lowest possible rate: a resolution of the Weitzman-Gollier puzzle - Mark C. Freeman (Kiel Institute for the World Economy (IfW), 2009)
In this paper the author proves that the Expected Net Future Value (ENFV) criterion can lead a risk neutral social planner to reject projects that increase expected utility. By contrast, the Expected Net Present Value (ENPV) rule correctly identifies the economic value of the project. While the ENFV increases with uncertainty over future interest rates, the expected utility decreases because of the planner's desire to smooth consumption across time. This paper therefore shows that Weitzman (1998) is right and that, within his economy, the far-distant future should be discounted at its lowest possible rate.
Keywords: D61; E43; G12; G31; Q51; 330; Discount rates; term structure; capital budgeting; interest rate uncertainty; environmental planning; Umweltplanung; Soziale Diskontrate; Investitionsrechnung; Zinsstruktur; Zinsrisiko; Theorie